Pengaruh Jumlah Cascade Dan Input Daya Terhadap Temperatur Thermoelectric Cooling Box Portable - M Akmal; Azridjal Aziz (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Thermoelectric cooling is heat pump based on peltier effect. The peltier effect occurs when two metals or semi-conductors of different materials are connected and energized that there will be a difference in temperature. This research is to know distribution of temperature on coldsink, heatsink and box. The experiment measuring temperature on 4 point with variation number of active cascade and input power on thermoelectric cooling box portable. It begin with 1 cascade, 2 cascade, and 3 cascade active, then variation input power with 50,5W, 72,72W and 113,64W. The results shows more and more number of active cascade actived, and increasing input power, temperature will colder.Keywords : Thermoelectric, Cascade, Input Power, Temperature